Evaluación agronómica de Cratylia argentea (Desvaux) O. Kuntze en Colombia - Maass, Brigitte L. (International Center for Tropical Agriculture, 1995)
The leguminous shrub Cratylia argentea has shown to be well adapted to acid, low-fertility soil environments in Colombia. A small germplasm collection of 11 accessions has been evaluated across different tropical environments in Colombia. However, the species revealed the most vigor in the humid tropics with relative fertile soils. Flowering and seed production have been proliferous in most environments tested. If scarified for sowing, viability of seed is strongly reduced. Issues for future research are listed.